Free Neurocognitive Screening Initiative: An Opportunity to Address Health Disparities and Promote Cultural Competence in Northcentral Florida. (30th August 2019) - Amofa Sr., P; Arias, F; Trifilio, E; Belser-Ehrlich, J; Rohl, B; Lopez, F; Levy, S-A
Abstract: Objective: The risk for cognitive impairment is greater in individuals with low SES and limited education. In rural areas, distance and economic concerns preclude individuals from accessing care. In Alachua County, 23% of residents live below poverty and 16% are uninsured. The Neurocognitive Screening Initiative (NSI) attempts to reduce disparities in Alachua by offering free neurocognitive screening. NSI also aspires to promote cultural competence through unique training opportunities for clinical neuropsychology doctoral students. Method: Patients learned about NSI through flyers, word of mouth, or referrals. Appointments include a clinical interview, cognitive testing, and mood questionnaires. Patients receive feedback, brain health recommendations, and referrals to community resources. Phase 1 began in November 2017 and involved selection of appropriate cognitive measures, development and dissemination of advertising materials, identification of resources, and trainee recruitment. From February 2018 to August 2018, phase 2 involved administration of cognitive screeners. Phase 3 involved continued provision of clinical services, expansion of the NSI team and increased culturally relevant outreach. Outcomes: NSI's greatest challenge is recruitment of the appropriate demographic. Since phase 2, we have evaluated 10 patients with diverse racial, socioeconomic, and clinical characteristics. NSI has recruited an ethnoracially diverse cohort of trainees comprised of 4 graduate students and 2 postdoctoral fellows supervised by a clinical neuropsychologist. Discussion: Efforts to provide services to marginalized individuals have uncovered challenges in attracting patients who might benefit from these services. NSI is forging community partnerships with churches, libraries, and local organizations to reach the targeted audience. Via weekly meetings, participation in community events/outreach, and clinical work, NSI provides unique training for emerging neuropsychologists.